2022
DOI: 10.3389/fcimb.2022.761604
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hcp Iron Ion Regulation on the Interaction Between Acinetobacter baumannii With Human Pulmonary Alveolar Epithelial Cells and Biofilm Formation

Abstract: Acinetobacter baumannii is a type of bacterial nosocomial infection with severe drug resistance. Hemolysin co-regulated protein (Hcp) is a marker of activated type VI secretion system (T6SS), a key secretory system that promotes Gram-negative bacteria colonization, adhesion, and invasion of host cells. Hcp is also regulated by iron ions (Fe). In this study, an ATCC17978 hcp deletion strain (ATCC17978Δhcp), an hcp complement strain (ATCC17978Δhcp+), and an A. baumannii–green fluorescent protein (GFP) strain wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…T6SS has been demonstrated to impact biofilm formation in several bacteria, such as Pseudomonas aeruginosa , Acinetobacter baumannii , and Burkholderia spp. ( Aubert Daniel et al, 2008 ; Schwarz et al, 2010 ; Moscoso et al, 2011 ; Pan et al, 2022 ). In V. cholerae , T6SS and biofilm formation are also connected as both negatively controlled by quorum sensing ( Hammer and Bassler, 2003 ; Zheng et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…T6SS has been demonstrated to impact biofilm formation in several bacteria, such as Pseudomonas aeruginosa , Acinetobacter baumannii , and Burkholderia spp. ( Aubert Daniel et al, 2008 ; Schwarz et al, 2010 ; Moscoso et al, 2011 ; Pan et al, 2022 ). In V. cholerae , T6SS and biofilm formation are also connected as both negatively controlled by quorum sensing ( Hammer and Bassler, 2003 ; Zheng et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Variation among infection and colonization found at different hospitals has been reported ( 20 ). Martín-Aspas et al ( 21 ) reported a 40% (49/122) Ab infection rate and a 60% (73/122) colonization rate while Rodríguez-Baño et al ( 22 ) found Ab colonization to be approximately 50% in some Spanish hospitals. Differences may be attributed to local socioeconomic conditions, hospital management, epidemiological differences, and patients’ basic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The T6SS is a gram-negative bacteria virulence system, which enables bacterial competition in the host, enhances invasiveness and adhesion, and improves bacterial viability within macrophages. T6SS is central to the pathogenesis of Ab infection (18)(19)(20)22,32,33). The T6SS marker, Hcp, shows different presence and expression levels in clinical isolates (11,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…However, few effectors associated with secretion systems, especially in T6SS, have been found to promote biofilm formation. Only VgrG and Hcp, which are both components and effectors of the T6SS, have been found to play positive roles in biofilm formation in bacteria (Sha et al 2013 ; Fei et al 2022 ; Pan et al 2022 ). TepB is the first identified enzymatic effector of T6SS that promotes biofilm formation during acute and chronic infections of P. aeruginosa PA14.…”
Section: Discussionmentioning
confidence: 99%